Pengaruh Metode Strutural Analitik Sintetik (SAS) Terharap Keterampilan Membaca Permulaan Siswa Kelas I SD Nurul Huda II Yapis Jayapura - Ernawati Ernawati; Tri Kurniah Lestari; Rezky Aprilyanto Wibowo; Nabila Nabila (Journal on Education, 2025)
This study aims to determine the effect of the Synthetic Analytic Structure (SAS) method on beginning reading skills in grade 1 students of SD Nurul Huda 2 Yapis in the 2023/2024 academic year. The results of this study are expected to be useful theoretically and practically. This type of research is experimental research with quasi-experimental research design. Data collection techniques are observation, documentation and tests. The data analysis technique uses the T test, namely the independent samples T test to determine whether there is an effect of learning using the Synthetic Analytic Structure (SAS) method on beginning reading skills. Based on the results of the study, the average value of beginning reading skills in the experimental class was 79.52 and the control class was 70.58. This is proven by the results of the posttest of students' beginning reading skills. The results of hypothesis submission obtained the value of tcount> ttable which is 2.272>1.671 and a significant value smaller than 0.05 which is 0.027. This shows that Ha is accepted and Ho is rejected. So it can be concluded that there is a positive and significant effect of learning using the Synthetic Analytical Structure (SAS) method on the beginning reading skills of grade 1 students of SD Nurul Huda 2 Yapis in the 2023/2024 academic year.